Closure of oroantral communications using a buccal graft of Bichat´s fat pedicled pad - Huapaya Paricoto de Murillo, Olinda (2012)
The buccal fat pad due to its size, vascular richness and versatility is a reliable flap. The technique which uses this anatomic element as flap is better tolerated by the patient, easy development and with fewer complications compared to other techniques. For the advantages of this technique is important to highlight its usefulness in the closure of oroantral comunications. This paper describes the technique used in a case of recurrent oroantral fistula which was recidivant to other treatments, treated in The National Institute of Child´s Health.